Incidence of Deep Vein Thrombosis and Associated Factors Among Intensive Care Unit Patients at Dhulikhel Hospital : A Prospective Cross-Sectional Study (Birat Journal of Health Sciences, 2025)
Introduction : Venous thromboembolism (VTE) is a common yet preventable complication in ICU patients. Prolonged immobilization, high disease severity scores such as APACHE II, and sepsis and invasive procedures contribute to the development of thromboembolism which can lead to life threatening conditions such as pulmonary embolism.Objectives: To evaluate the incidence of deep vein thrombosis (DVT) among ICU admitted patients and identify its associated factors.Methodology:  We conducted a prospective cross-sectional study on 59 ICU patients. The data included demographics, comorbidities, operative procedures, D-dimer levels, thrombo-prophylaxis, lower limb ultrasound  and doppler findings.Results: The incidence of DVT among ICU patients was 5.1% (3/59; 95% CI: 1.1%-14.2%) , with all cases occurring despite pharmacological thromboprophylaxis. Elevated D-dimer (>0.5 mcg/mL) was observed in two-thirds of DVT cases, though no significant association was found between D-dimer levels and DVT incidence. Common comorbidities were sepsis (63%), pneumonia (27.1%), and COPD (25%). Twenty two percent of patients underwent operative procedures out of which one developed DVT. There was higher prevalence of DVT in older age groups (12.5% in patients >75 years) and females (11.1%). Smoking, blood transfusion and sepsis were clinically relevant factors, aligning with global risk profiles. Conclusion: The incidence of DVT was significant among ICU patients at Dhulikhel Hospital. Close monitoring of  critically ill patients with target screening strategies and individual risk assessment help to improve early detection and prevention.